Case Report: Adjuvant Crizotinib Therapy Exerted Favorable Survival Benefit in a Resectable Stage IIIA NSCLC Patient With Novel LDLR–ROS1 Fusion - Chen, An-guo; Chen, Dong-sheng; Li, Si; Zhao, Le-le; Xiao, Ming-zhe (Frontiers in Oncology, 2022)
Novel adjuvant strategies are needed to optimise outcomes after complete surgical resection in patients with early-stage non-small-cell lung cancer (NSCLC). The adjuvant treatment of ROS Proto-Oncogene 1 (ROS1) fusion-positive resected NSCLC is challenging because there is no curative confirmed randomized controlled trial. Next-generation sequencing (NGS) and immunohistochemistry (IHC) staining were performed on the biopsy sample. In this case, we identified a novel LDLR-ROS1 fusion in aresectable stage IIIA NSCLC patient. The patient received crizotinib as adjuvant treatment and achieved recurrence-free survival (RFS) for 29 months, without significant symptoms of toxicity. In this case, we report a novel LDLR-ROS1 fusion responding to crizotinib in a patient with lung adenocarcinoma, supporting the use of adjuvant treatment with ROS1 inhibitor exerting clinical survival benefit in ROS1 fusion-positive resected NSCLC.